2015
DOI: 10.11607/prd.1861
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Peri-implant Bone Defects with Platelet-Rich Fibrin

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 0 publications
3
62
0
1
Order By: Relevance
“…2015, Öncü & Alaadinŏglu 2015) evaluated the benefits of the application of L‐PRF on the osseointegration process (Table 3). Öncü & Alaadinŏglu (2015) evaluated the impact of implant coating with L‐PRF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2015, Öncü & Alaadinŏglu 2015) evaluated the benefits of the application of L‐PRF on the osseointegration process (Table 3). Öncü & Alaadinŏglu (2015) evaluated the impact of implant coating with L‐PRF.…”
Section: Resultsmentioning
confidence: 99%
“…Hamzacebi et al. (2015) assessed the effectiveness of the application of L‐PRF and conventional flap surgery for the treatment of peri‐implantitis bone loss. They reported more PD reduction (at 3 and 6 months: L‐PRF sites: 2.4 ± 1.1 mm and 2.8 ± 1.0 mm, non‐L‐PRF sites: 1.65 ± 1.0 mm and 2.0 ± 0.7 mm), and CAL gain (L‐PRF sites: 2.9 ± 1.0 mm, non‐L‐PRF sites: 1.4 ± 1.0 mm).…”
Section: Resultsmentioning
confidence: 99%
“…PRF increased the probing depth reduction, increased the gain in clinical attachment and reduced mucosal recession after 3 and 6 months (Hamzacebi et al., 2015). …”
Section: Resultsmentioning
confidence: 99%
“…One approach might be the use of PRF. Only one RCT, with a 6‐month follow‐up, observed the effect of PRF in peri‐implantitis defects (Hamzacebi et al., 2015). Although a significant improvement of pocket reduction, clinical attachment gain, and mucosal recession was found in the PRF group, it is not possible to draw a definitive conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Masuki et al21 stated that CGF and A-PRF have a similar capacity for inducing angiogenesis and subsequent wound healing/tissue regeneration, which is better than the results of platelet-rich plasma (PRP). A randomized, controlled, clinical trial evaluated the effect of PRF combined with flap surgery for the treatment of peri-implant bone loss and concluded that the additional use of PRF provided significant improvements in CAL gain 36. Moreover, it should be kept in mind that bone healing in intrabony periodontal defects is different from that of PBD due in particular to the differences in blood supply of the periodontium during the healing period.…”
mentioning
confidence: 99%